2013
DOI: 10.3168/jds.2011-5051
|View full text |Cite
|
Sign up to set email alerts
|

Random regression models using Legendre polynomials or linear splines for test-day milk yield of dairy Gyr (Bos indicus) cattle

Abstract: Studies investigating the use of random regression models for genetic evaluation of milk production in Zebu cattle are scarce. In this study, 59,744 test-day milk yield records from 7,810 first lactations of purebred dairy Gyr (Bos indicus) and crossbred (dairy Gyr × Holstein) cows were used to compare random regression models in which additive genetic and permanent environmental effects were modeled using orthogonal Legendre polynomials or linear spline functions. Residual variances were modeled considering 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
23
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 28 publications
14
23
0
6
Order By: Relevance
“…(Tables 3 and 4). The genetic correlation estimates obtained with the RRMs were high and near the unity for the adjacent records, with the values declining as the interval between the test-day records increased (Tables 3). The same tendency was reported by Bignardi et al (2009) for the Holstein breed, by Kettunen et al (2000) for the Ayrshire breed, by Herrera et al (2008), and Pereira et al (2013b) for the Gyr breed, and Santos et al (2013a) for the Guzerat breed, all of them using parametric function. The three RRMs (Leg.3.5.6, Leg.3.6.6 and Leg.6.6.6) showed negative genetic correlation estimates between milk yield in the first and in the last test-day records, but of small magnitudes.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…(Tables 3 and 4). The genetic correlation estimates obtained with the RRMs were high and near the unity for the adjacent records, with the values declining as the interval between the test-day records increased (Tables 3). The same tendency was reported by Bignardi et al (2009) for the Holstein breed, by Kettunen et al (2000) for the Ayrshire breed, by Herrera et al (2008), and Pereira et al (2013b) for the Gyr breed, and Santos et al (2013a) for the Guzerat breed, all of them using parametric function. The three RRMs (Leg.3.5.6, Leg.3.6.6 and Leg.6.6.6) showed negative genetic correlation estimates between milk yield in the first and in the last test-day records, but of small magnitudes.…”
Section: Resultssupporting
confidence: 64%
“…Also Pereira et al (2010) observed the similar estimates as the ones of the present study, but in a lager range (0.09 to 0.33). Costa et al (2005), using Legendre polynomials for the Gyr breed, found higher heritability values, which ranged from 0.71, at the start, to 0.21 at the end of lactation, while Pereira et al (2013aPereira et al ( , 2013b found lower estimates, which ranged from 0.12 to 0.24 and from 0.12 to 0.26, respectively. These last authors used Spline function for estimating heritabilities, which ranged from 0.16 to 0.29 .…”
Section: Resultsmentioning
confidence: 99%
“…O pico de produção ocorreu, em média, entre os dias 35 e 79 da lactação, mais tarde do que o relatado por Pereira et al (2013aPereira et al ( , 2013b e a fase da lactação. Nas DIF analisadas dentro de cada fase da lactação (Tabela 2), observaram-se diferenças entre as classes de ∆F i .…”
Section: Resultsunclassified
“…A e p são, respectivamente, as matrizes de covariâncias genético-aditivas e de ambiente permanente entre os coeficientes de regressão; R é a matriz de variâncias residuais, que é uma matriz diagonal com componentes de variância específicos para os intervalos 5-30, 31-60, 61-120, 121-270 e 271-305 dias em lactação, conforme descrito por Pereira et al (2013b). Além disso, assumiu-se que os resíduos para diferentes dias da lactação eram não correlacionados.…”
Section: Methodsunclassified
See 1 more Smart Citation